Family Nursing Care for Cerebrovascular Accident (CVA) Patients: A Case Report - Prayitno, Eko (Health Gate, 2025)
Cerebrovascular Accident is a neurological deficit disease caused by bleeding or blockage with symptoms and signs according to the affected part of the brain, which can cause disability or death. The assessment found several complaints in the form of weakness of the extremities, not taking medication regularly, and the family did not know the care for family members with CVA. The nursing diagnosis in CVA patients is impaired physical mobility, ineffective family health management, and readiness to increase knowledge. The interventions determined for CVA patients are based on the previous diagnosis and theory. The implementation carried out on CVA patients is based on the previously determined interventions and is adjusted to the conditions and situations of the patient. Evaluation of CVA patients during two meetings found that the problem of ineffective family health management nursing was resolved, the problem of readiness to increase knowledge was resolved, and the problem of impaired physical mobility nursing was partially resolved due to time constraints in implementing it.